2022
DOI: 10.1186/s12871-022-01685-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting difficult laryngoscopy in morbidly obese Thai patients by ultrasound measurement of distance from skin to epiglottis: a prospective observational study

Abstract: Background In morbidly obese patients, airway management is challenging since the incidence of difficult intubation is three times than those with a BMI within the healthy range. Standard preoperative airway evaluation may help to predict difficult laryngoscopy. Recent studies have used ultrasonography-measured distance from skin to epiglottis and pretracheal soft tissue at the level of vocal cords, and cut-off points of 27.5 mm and 28 mm respectively have been proposed to predict difficult lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A similar study from Thailand on morbidly obese patients concluded that distance from skin to epiglottis could predict difficult laryngoscopy. [ 16 ] In our study, BMI was significantly higher in the difficult airway group [ P = 0.009; Table 2 ]. DSTI is a better predictor of difficult airways and is better correlated with clinical assessment tools for difficult airways.…”
Section: Discussionmentioning
confidence: 64%
“…A similar study from Thailand on morbidly obese patients concluded that distance from skin to epiglottis could predict difficult laryngoscopy. [ 16 ] In our study, BMI was significantly higher in the difficult airway group [ P = 0.009; Table 2 ]. DSTI is a better predictor of difficult airways and is better correlated with clinical assessment tools for difficult airways.…”
Section: Discussionmentioning
confidence: 64%
“…Neck circumference (> 42 cm), together with BMI (> 50 kg/m2), were independent predictors of difficult intubation in morbidly obese patient population [29]. Various clinical parameters, such as abundance of pretracheal soft tissue at the level of the vocal cords [30], age, thyromental distance and ultrasonography for the distance from skin to epiglottis [31], have been used to predict difficult tracheal intubation in obese patients (more proposed predictors details are shown in Table 1).…”
Section: Obesity and Difficult Airwaymentioning
confidence: 99%
“…However, we found no association between Pre-E/E-VC ratio >1 and difficult intubation. Airway ultrasound, which provides accurate dimensions of the Pre-E, is still used to predict difficult laryngoscopy in morbidly obese patients in our setting 30 , but new staff need to practice regularly so that they gain more experience. Future studies with larger sample sizes should be conducted to better assess the association between Pre-E/E-VC and difficult intubation.…”
Section: Study Implications and Clinical Usementioning
confidence: 99%